2,4,3',4'-tetramethoxy-biphenyl induces apoptosis in MGC-803 cells through a mitochondrial/caspase pathway (Bangladesh Journal of Pharmacology, 2014)
Anti-proliferative and apoptosis-inducing effects of 2,4,3?,4?-tetramethoxy-biphenyl (TMBP) on human gastric cancer MGC-803 cells were investigated. The molecular mechanisms of TMBP-mediated tumor cell death were detected by clonogenic assay, staining with Hoechst 33258, DNA fragmentation assay, Western blot analysis and flow cytometry assay. Studies on MGC-803 cells treated with TMBP showed that TMBP inhibited the proliferation of MGC-803 cells in a time- and dose-dependent manner. The induction of apoptosis by TMBP was accompanied by the loss of mitochondrial membrane potential (ΔΨm), cytochrome C release and activation of caspase cascade, resulting in the cleavage of some specific substrates for caspase-3 such as poly (ADP-ribose) polymerase (PARP). In conclusion, these findings showed that TMBP may induce the apoptosis of MGC-803 through a mitochondrial/caspase pathway, suggesting its possible use for treating human cancers.